A sanguinicolid blood fluke in sea bass (lates calcarifer bloch) in coastal peninsular Malaysia - Herbert, Brett W. (Universiti Pertanian Malaysia, 2012)
Cruoricola lates N. Gen., N. Sp. from the blood vessels of cultured sea bass (Lates calcarifer Bloch 1790) is described.